Implementation of Profitability on Dividend Distribution and Company Value on the Jakarta Islamic Index - Jariah, Putri Ainun; Laba, Abd. Rakhman; Aswan, Andi (Manunggal Halim Jaya, 2025)
This study aims to determine the effect of liquidity, profitability on firm value and dividend policy as a mediating variable (Study on the Jakarta Islamic Index 2016-2020). This type of research is descriptive quantitative research using secondary data from financial statements as a source of data collection. Focus on research related to social humanities, with a research theme focused on finance that is more specific to financial reports within the corporate scope of the 2017-2021 Jakarta Islamic index as a research topic. This research uses path analysis technique. The results of this study indicate that 1) Liquidity has a significant negative effect on dividend policy. 2) Profitability has a significant positive effect on dividend policy. 3) Liquidity has no significant negative effect on firm value. 4) Profitability has a significant positive effect on firm value. 5) Dividend policy has a significant positive effect on firm value. 6) Liquidity has a significant negative effect on firm value through dividend policy. 7) Profitability has a significant positive effect on firm value through dividend policy.